ANALISIS FAKTOR-FAKTOR KESULITAN MEMBACA PERMULAAN SISWA KELAS I SDN KUNCIRAN 2 KOTA TANGERANG - Perdana, Arza Amelia; Boy Dorahman; Rahmawati Eka Saputri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the factors of initial reading difficulties of first-grade students at SDN Kunciran 2 Tangerang City. This study uses a descriptive qualitative research method. The subjects in this study were teachers and first-grade students who experienced initial reading difficulties with categories of obtaining high, medium, and low scores. Data collection techniques used oral tests, observation, interviews, and documentation. Furthermore, the data were analyzed using the Miles and Huberman model analysis technique with 3 stages, namely data reduction, data presentation, and conclusion drawing. The results of the research conducted by the researcher were that there were 10 students who experienced initial reading difficulties, including 3 students who obtained high scores, 3 students who obtained medium scores, and 4 students who obtained low scores. The factors that became the initial reading difficulties were the omission of words or letters, pronunciation of words with teacher assistance, hesitation, not being able to recognize letters, not being able to read syllables, not being able to read words per word, not being able to read sentences, not being able to spell, not paying attention to punctuation, lack of confidence, lack of focus (concentration), lack of attention from parents, and halting reading. Therefore, researchers can draw the conclusion that there are still students who are not yet fluent in reading at the beginning, this is caused by a lack of motivation in learning, family environment, and the unavailability of reading materials.